RANCANG BANGUN APLIKASI BERBASIS ANDROID UNTUK BRAND CLOTHING SAND BEACH DENGAN SKEMA DISKON MENGGUNAKAN HUNGARIAN ALGORITHM - Ibrahim, Kelvin Adha Bilqis; Dian, Gustina (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2021)
AbstractThese days, the world of technology is evoluting and growing rapidly. One of the most evoluted is android. Beside technology, fashion sector also become one of the most grow sector. The most common problem in this field is marketing. These era of evolution have created fierce creative competition as well. The media in making sales is an important aspect that can attract buyers and increase the profit. Mobile application is the process by which application development for handheld devices such as cell phones or PDAs. During manufacturing, mobile applications already exist or can be downloaded by the user according to the software platform. An Android-based Brand Clothing of Sand Beach application with a discount scheme using a hungarian algorithm. Hungarian algorithm is a suitable method to determine which discount is the most profitable for buyers so that could attracts buyers to clothing brands that are in this application. This Android-based application contains information about products that are neatly packaged and attractive to make it easier for buyers to see clearly the descriptions, models, and prices of the products they want to buy. This Android-based Clothing Brand of Sand Beach application also has an admin account that can access and manage orders from buyers in an orderly and systematic manner.Â Keyword : Application, Hungarian Algorithm, Shop, Discount Scheme, Android, Fashion Brand.